2021
DOI: 10.1080/25785826.2021.1930371
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive immunity in the joint of rheumatoid arthritis

Abstract: Adaptive immunity plays central roles in the pathogenesis of rheumatoid arthritis (RA), as it is regarded as an autoimmune disease. Clinical investigations revealed infiltrations of B cells in the synovium, especially those with ectopic lymphoid neogenesis, associate with disease severity. While some B cells in the synovium differentiate into plasma cells producing autoantibodies such as anti-citrullinated protein antibody, others differentiate into effector B cells producing proinflammatory cytokines and expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 115 publications
0
11
0
Order By: Relevance
“…It was reported that IL-4 produced by Th2 T cells inhibits OCs formation and function in vitro [86,99,100]; nonetheless, no functional activity has been reported in vivo. On the other hand, Th1 CD4 + T cells, which counter regulate Th2 cells, are found in the synovium fluid of patients with active RA [101], although it has been demonstrated that the secretion of IFN-γ by this T cell subset strongly inhibits osteoclastogenesis and protects against bone tissue degradation by OCs [102].…”
Section: Role Of T and B Cells In Bone Disordersmentioning
confidence: 99%
See 3 more Smart Citations
“…It was reported that IL-4 produced by Th2 T cells inhibits OCs formation and function in vitro [86,99,100]; nonetheless, no functional activity has been reported in vivo. On the other hand, Th1 CD4 + T cells, which counter regulate Th2 cells, are found in the synovium fluid of patients with active RA [101], although it has been demonstrated that the secretion of IFN-γ by this T cell subset strongly inhibits osteoclastogenesis and protects against bone tissue degradation by OCs [102].…”
Section: Role Of T and B Cells In Bone Disordersmentioning
confidence: 99%
“…It is clear now that the identity of T cell subsets is critical in guiding their role on bone remodeling system, during homeostasis or in pathological conditions [67]. In particular, Th1, Th2, Th17, Th22, and T reg CD4 + and CD8 + cells have been shown to influence bone metabolism [67,[86][87][88][89]. In the RA scenario-the best studied human disease in osteoimmunology-the importance of Th17 CD4 + T cells is evident, beginning by their infiltration into the synovium and the association of disease susceptibility with specific variants of T-cells-related genes, such as HLA-DR (MHC class II cell surface receptor encoded by the human leukocyte Ag gene complex), Protein Tyrosine Phosphatase Non-Receptor Type 22 (PTPN22), and C-C Motif Chemokine Receptor 6 (CCR6) [40,63].…”
Section: Role Of T and B Cells In Bone Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…Adaptive immunity plays a central role in the pathogenesis of RA. Synovial T cells are involved in the induction of antibody production and local inflammation ( 198 ). In particular, CD4 + T cell subsets can differentiate to produce a variety of pro-inflammatory cytokines and chemokines, which are involved in the pathogenesis of RA.…”
Section: Mechanism Of Action Against Ramentioning
confidence: 99%